Potential Epigenetic-Based Therapeutic Targets for Glioma - Zang, Lanlan; Kondengaden, Shukkoor Muhammed; Che, Fengyuan; Wang, Lijuan; Heng, Xueyuan (Frontiers in Molecular Neuroscience, 2018)
Glioma is characterized by a high recurrence rate, short survival times, high rates of mortality and treatment difficulties. Surgery, chemotherapy and radiation (RT) are the standard treatments, but outcomes rarely improve even after treatment. With the advancement of molecular pathology, recent studies have found that the development of glioma is closely related to various epigenetic phenomena, including DNA methylation, abnormal microRNA, chromatin remodeling and histone modifications . Owing to the reversibility of epigenetic modifications, the proteins and genes that regulate these changes have become new targets in the treatment of glioma. In this review, we present a summary of the potential therapeutic targets of glioma and related effective treating drugs based on epigenetics from four aspects. We further illustrate how epigenetic mechanisms dynamically regulate the pathogenesis and discuss the challenges of glioma treatment. Currently, among epigenetic treatments, DNA methyltransferase (DNMT) inhibitors and histone deacetylase inhibitors (HDACIs) can be used for the treatment of tumors, either individually or combination. In the treatment of glioma, only HDACI remain good option andthey provide new directions for the treatment of glioma. Due to the complicated pathogenesis of glioma, epigenetic applications to glioma clinical treatment are still limited.